2022
DOI: 10.1002/jmv.28017
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of distinct Omicron sublineages by longitudinal vaccination sera

Abstract: To the Editor, The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron (BA.1) variant was first identified in Botswana and South Africa in November 2021, and it soon replaced the Delta variant as the dominant global variant. 1 Many new Omicron sublineages, including BA.2, BA.2.12.1, BA.4, and BA.5, continue to evolve with enhanced neutralization escape capabilities, 2 posing serious challenges to the neutralization efficacy of current COVID-19 vaccines and antibody therapeutics. We and others … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…All convalescents had reported mild symptoms or were asymptomatic. On Vero-E6 cells, we observed significantly lower luciferase levels in vaccination (Figure 1A, red lines) or convalescent (Figure 1B, red lines) sera compared to healthy control sera (black lines), indicating the viral neutralization activities of the vaccination/convalescent sera, similar to what we previously reported [26][27][28][29]. However, when we tested them on Raji cells, which are cloned B cells highly expressing FcγRIIB [30], we found that both vaccination and convalescent sera (Figure 1C,D, red lines), at certain concentrations, significantly increased luciferase signals compared to control sera (black lines) using the same SARS-CoV-2 D614G pseudovirus.…”
Section: Vaccination and Convalescent Sera From Covid-19 Patients Ind...supporting
confidence: 87%
“…All convalescents had reported mild symptoms or were asymptomatic. On Vero-E6 cells, we observed significantly lower luciferase levels in vaccination (Figure 1A, red lines) or convalescent (Figure 1B, red lines) sera compared to healthy control sera (black lines), indicating the viral neutralization activities of the vaccination/convalescent sera, similar to what we previously reported [26][27][28][29]. However, when we tested them on Raji cells, which are cloned B cells highly expressing FcγRIIB [30], we found that both vaccination and convalescent sera (Figure 1C,D, red lines), at certain concentrations, significantly increased luciferase signals compared to control sera (black lines) using the same SARS-CoV-2 D614G pseudovirus.…”
Section: Vaccination and Convalescent Sera From Covid-19 Patients Ind...supporting
confidence: 87%
“…Much lower neutralizing activity was found against the Omicron sublineages compared to WT and Delta variants, with 6.3-to 9.2-fold reduction compared to WT. Consistent with the trend we found for the 3-dose vaccination sera, 7,8 Omicron BA.1 and BA.2 comparably evaded serum neutralization, and of the three sublineages that evolved from BA.2, BA.2.12.1 exhibited a similar degree of immune evasion compared to BA.2, while BA.2.75 and BA.4/5 showed even lower neutralization titers than those of BA.2 (Figure 1B, left panel).…”
supporting
confidence: 91%
“…The rapid and widespread transmission of SARS-CoV-2 has led to the emergence of multiple variants of concern (VOCs), most notably Omicron variant, which continues to evolve and diversify into a range of sub-lineages. Our previous research has shown that these Omicron sub-lineages, spanning BA.1 to BA.2.86, have been evolving to exhibit increased neutralization escape capabilities [1][2][3][4][5] . Since November 2023, the JN.1 variant, stemming from BA.2.86's antigenic diversity and acquiring an additional mutation (L455S) in RBD, has rapidly emerged as the dominant strain (Fig.…”
Section: Introductionmentioning
confidence: 99%